Green Micro- and Nanoemulsions for Managing Parasites, Vectors and Pests - Lucia Pavoni; Roman Pavela; Marco Cespi; Giulia Bonacucina; Filippo Maggi; Valeria Zeni; Angelo Canale; Andrea Lucchi; Fabrizio Bruschi; Giovanni Benelli (Nanomaterials, 2019)
The management of parasites, insect pests and vectors requests development of novel, effective and eco-friendly tools. The development of resistance towards many drugs and pesticides pushed scientists to look for novel bioactive compounds endowed with multiple modes of action, and with no risk to human health and environment. Several natural products are used as alternative/complementary approaches to manage parasites, insect pests and vectors due to their high efficacy and often limited non-target toxicity. Their encapsulation into nanosystems helps overcome some hurdles related to their physicochemical properties, for instance limited stability and handling, enhancing the overall efficacy. Among different nanosystems, micro- and nanoemulsions are easy-to-use systems in terms of preparation and industrial scale-up. Different reports support their efficacy against parasites of medical importance, including Leishmania, Plasmodium and Trypanosoma as well as agricultural and stored product insect pests and vectors of human diseases, such as Aedes and Culex mosquitoes. Overall, micro- and nanoemulsions are valid options for developing promising eco-friendly tools in pest and vector management, pending proper field validation. Future research on the improvement of technical aspects as well as chronic toxicity experiments on non-target species is needed.